CHARACTERISTICS OF THE STATE POLICY REGULATING THE DEVELOPMENT OF TOURISM IN THE CARPATHIAN REGION OF UKRAINE - RAKOWSKA, Joanna; IABLON, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article focuses on issues of theoretical and methodological foundations of functioning and development of tourism in the region. The general problems of the functioning and development of tourism in the Carpathian region of Ukraine are defined.  The purpose of the article is to characterize and identify problematic aspects of the state policy of regulating tourism development in the Carpathian region of Ukraine. It has been proven that the quality of the state policy regarding the formation and development of the tourist complex of the Carpathian region of Ukraine can be considered high and such that to a certain extent it contributed to the progress of this sector of the regional economy, the improvement of its institutional capacity, the development of infrastructure, etc. A separate strength of regional policy in this area should be considered the presence of specialized bodies at the level of regional state military administrations of all regions of the region, as well as the implementation of regional programs for the development of tourism and resorts. This is evidence of the institutionalization and practice of planning tourism development policy in the region. On the other hand, regional policy in the analyzed area is still characterized by such weaknesses as the limitation of statistical data, the absence of a system for monitoring quality parameters of the implementation and development of tourist activities in certain types of tourism; part of the measures envisaged by the regional tourism development programs are declarative, and their expected indicators are not scientifically based and are not forecast; a full-fledged institutional and organizational system for ensuring the development of tourism has not been built; the business environment is still not favorable for public investment in the tourism business; there is no system for monitoring the business environment, factors and obstacles to the functioning and development of elements of the tourist complex. The presence of these weak points activates the action of a number of challenges and threats, which can lead to the absence of data on the real state and trends of tourism development in the region, the shadowing of the activities of accommodation facilities, the strengthening of structural imbalances and the lack of systemic progress of the complex, the replacement of the initiating and coordinating functions of tourism administrations purely representative, chaotic development of individual segments of tourism as a whole.
Keywords: tourism; Carpathian region; development management; tourism policy; tourism infrastructure